Validity and reliability of mathematics learning strategy instruments among middle school students in Jordan - Rabab’h, Belal Sadiq Hamed; Veloo, Arsaythamby (Canadian Center of Science and Education, 2014)
This study aimed to determine the validity and reliability of Mathematics Learning Strategy (MLS) for Jordanianstudents, and to identify the relationship between factors of MLS instrument. The MLS was used to measureindividual behavior based on five factors of mathematics (attitude, motivation, self-regulation, self-efficacy andanxiety).The previous study used 83 items to assess the MLS. Finding from Factor analysis indicated that allfive factors items of MLS instrument ranged from 66.29% to 69.35% of the total variance indicating that allfactors are related and thus represent a valid measure of MLS. The reliability of each factor was justified interms of its internal consistency by means of Cronbach Alpha.Pearson correlation coefficient shows positive,strong correlation between five factors.Findings of this study confirmed the validity and reliability of the finalMLS instrument with 65 items, and indicated that it is a useful instrument to evaluate the MLS among middleschool students in Jordan.Thus, the instrument can be used by teachers, counselors and principals inunderstanding student MLS. With such understanding, teachers can easily engage in effective mathematicsteaching.